Indigenous peoples and religious change - Brock, Peggy (Studies in Christian mission 0924-9389, 2005)
"This book explores a range of societies in and around the Pacific and southern Africa in the nineteenth and twentieth centuries that encountered religions introduced from elsewhere, or fashioned their own responses to already established religious traditions. These changes observed through the responses of the receiving societies indicate that religious change is a creative dynamic, rather than a passive acceptance of new ideas, beliefs and practices."--Jacket